Evidence of Hepatitis E virus breaking through the blood–brain barrier and replicating in the central nervous system. Issue 11 (21st June 2016) - Shi, R.; Soomro, M. H.; She, R.; Yang, Y.; Wang, T.; Wu, Q.; Li, H.; Hao, W.
Summary: Neurologic dysfunctions such as Guillain–Barre′ syndrome, encephalitis, meningitis and transverse myelitis occur frequently in patients with hepatitis E virus (HEV) infection, and this study was conducted to better characterize the role of HEV in the pathogenesis of neurologic disorders. Genotype 4 strain of swine HEV was used to inoculate Mongolian gerbils. Reverse transcription–nested polymerase chain reaction (RT‐nPCR), ELISA, histopathology, ultrastructural pathology and enzyme immunohistochemistry method were conducted to investigate the replication and localization of HEV in the central nervous system (CNS) and the consequent pathological changes. Both positive‐ and negative‐strand HEV RNA was detectable in brain and spinal cord from 7 to 28 dpi (days postinoculation) via RT‐nPCR. Various pathological changes such as perineural invasion, neuron necrosis, microglia nodule, lymphocyte infiltration, perivascular cuff and myelin degeneration were observed in HEV‐positive brains and spinal cords. Immunohistochemical (IHC) staining targeting on HEV ORF2 protein revealed positive signals concentrated mainly in the cytoplasm of neuron, ependymal epithelium and choroid plexus area. Positive area density of ZO‐1 (zonula occludens‐1) in brain of HEV‐positive gerbils decreased, while the GFAP (glial fibrillary acidic protein) expression was upregulated compared with control groups. These results provide strong evidence that HEV is able to damage the blood–brain barrier (BBB), replicate in brain and spinal cord, and hammer the causative role of HEV in the pathogenesis of neurologic disorders.